Upaya Meningkatkan Minat Belajar dan Keterampilan Menulis Pantun Melalui Model Think Talk Write (TTW) pada Mata Pelajaran Bahasa Indonesia Kelas V Sekolah Dasar - Bayu Widodo; Agustina Tyas Asri Hardini (Melati Institute, 2024)
This research aims to increase the interest in learning and the skills of writing rhyme in class V students by using the Think Talk Write (TTW) model. This research is a Classroom Action Research. The instruments used are questionnaires, observations, and test questions. The data analysis technique employed is a descriptive quantitative approach. The success indicator of this research is a 20% increase in learning interest and rhyme writing skills. The results of this research indicate that, in the final action, there was an increase in learning interest by 33%, reaching 90%. Meanwhile, rhyme writing skills improved by 27%, reaching 87%.